Neuropeptide GPCRs in Neuroendocrinology - Jae Young Seong; Hubert Vaudry (Frontiers Media SA, 2021)
The human genome encompasses ~ 860 G protein-coupled receptors (GPCRs) including 374 non-chemosensory GPCRs. Half of these latter GPCRs recognize (neuro)peptides as natural ligands. GPCRs thus play a pivotal role in neuroendocrine communication. In particular, GPCRs are involved in the neuroendocrine control of feeding behavior, reproduction, growth, hydromineral homeostasis and stress response. GPCRs are also major drug targets and hence possess a strong potential for the development of innovative pharmaceuticals. The aim of this Research Topic was to assemble a series of review articles and original research papers on neuropeptide GPCRs and their ligands that would illustrate the different facets of the studies currently conducted in this domain.